2021
DOI: 10.1155/2021/5525354
|View full text |Cite
|
Sign up to set email alerts
|

Financial Risk Early-Warning Model Based on Kernel Principal Component Analysis in Public Hospitals

Abstract: Public hospitals are facing the dual pressure of coping with external medical market competition and performing public health duties. Due to the influence of various risk factors, public hospitals are facing increasing financial risks. How to effectively prevent and control financial risks and maintain the normal operation and sustainable development of the hospital is a very important topic that needs to be studied in the development of public hospitals. Because the traditional principal component analysis me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…For the SC Group's financial early warning model, Pompella and Dicanio recommended integrating the logistic regression method with the factor analysis method to increase the model's accuracy [ 19 ]. Qu and Li suggested that the addition of annual cumulative excess return of nonfinancial indicators and auditor's opinions improved the prediction accuracy of the model [ 20 ]. Zhu and Liu suggested that there are not only financial indicators but also nonfinancial indicators that affect the evaluation of the company's business performance.…”
Section: Related Workmentioning
confidence: 99%
“…For the SC Group's financial early warning model, Pompella and Dicanio recommended integrating the logistic regression method with the factor analysis method to increase the model's accuracy [ 19 ]. Qu and Li suggested that the addition of annual cumulative excess return of nonfinancial indicators and auditor's opinions improved the prediction accuracy of the model [ 20 ]. Zhu and Liu suggested that there are not only financial indicators but also nonfinancial indicators that affect the evaluation of the company's business performance.…”
Section: Related Workmentioning
confidence: 99%
“…Financial issues are the key concern of every listed company. e establishment of a financial risk prediction system can effectively avoid the company's financial crisis and promote the company's sustainable development [9]. If the financial risks that the company will face in the future can be predicted, the company can greatly avoid losses and protect the company's interests.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of financial alert first appeared in western countries. At present, the theory of financial crisis is constantly improving, and there are many research results in the research and analysis of financial distress [1]. From the perspective of fiscal forewarning, early research mainly depends on personal development experience, and there will always be some deviation in financial alert [2].…”
Section: Introductionmentioning
confidence: 99%